2007
DOI: 10.1590/s1415-790x2007000400015
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of enteroparasites among school children from Guarapuava, State of Paraná, Brazil

Abstract: The most common infections in human beings are caused by intestinal parasites. They can lead to a number of harmful effects, which could include, among others, intestinal obstruction, malnutrition, iron deficiency anemia, diarrhea, and poor absorption. In Brazil, enteroparasites are one of the main public health issues. The present study aims at analyzing the distribution and frequency of enteroparasite occurrence in 635 children from seven community schools in the city of Guarapuava, Paraná (PR). In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
14

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 24 publications
2
12
0
14
Order By: Relevance
“…Castro et al [30] and Buschini et al [31] found in school communities in different regions of Brazil respectively 10.8% and 26.7% of parasite association of intestinal parasites, a high level as found also found in children of the community of Saurimo, Angola.…”
Section: Discussionmentioning
confidence: 79%
“…Castro et al [30] and Buschini et al [31] found in school communities in different regions of Brazil respectively 10.8% and 26.7% of parasite association of intestinal parasites, a high level as found also found in children of the community of Saurimo, Angola.…”
Section: Discussionmentioning
confidence: 79%
“…The studies suggest that geo-helminths represent a major public health problem and are an important indicator of the sanitary conditions in which a certain population lives. The association between the prevalence of intestinal parasitic diseases with socioeconomic and environmental factors was reported in the most of researches like: children from slums [71] or residing in townships with a low HDI in the N and NE regions, especially in rural areas [74]; households with no proper waste management and no solid residue collection [78]; the unhealthy condition to which this population is subjected [72,87], with a direct relationship with low maternal schooling [81,95] and low income family [80,[85][86][87][88][89][90][91]95]. The higher prevalence of Ascaris lumbricoides, Giardia duodenalis, Trichuris trichiura and hookworm infections in children living in contaminated environments [75,90,92,93] with inadequate daily caloric intake [94] may result in hospitalizations due to diarrheal disease [79], compromising their future anthropometric status [76,94].…”
Section: A Study On Incidence Of Clinical Hypoxic Ischemic Encephalopmentioning
confidence: 99%
“…Creche Apesar de alguns estudos mostrarem uma maior prevalência em crianças do sexo masculino 1,4,5,11 , os resultados desta pesquisa apontaram que a infecção nas crianças do sexo feminino foi mais prevalente, ainda que existam trabalhos que não fazem referência entre as possíveis diferenças de prevalência de parasitoses intestinais em relação ao sexo das crianças 12,13,14 .…”
Section: Parasitosunclassified
“…É unânime que os dois protozoários mais prevalentes no estudo (G. lamblia e E. coli), bem como Hymenolepis nana e A. lumbricoides estão relacionados às condições ambientais, falta de hábitos de higiene e de saneamento básico, confinamento em creches e asilos, contaminação do depósito sub-ungueal, ingestão de água e alimentos contaminados, contato com o solo e à precariedade da educação sanitá-ria 1,5, 8,13,15 .…”
Section: Parasitosunclassified
See 1 more Smart Citation